A Game-theoretic Analysis of Hybrid Threats. Issue 1 (2nd January 2022) - Balcaen, Pieter; Bois, Cind Du; Buts, Caroline
ABSTRACT: For decades, the concept of deterrence and the fear for nuclear confrontation withheld large powers from waging aggression against each other. Recent technological developments and the growing interconnectedness however allowed some states to find ways to challenge the West by using so called 'hybrid threats'. This way of waging war entails the synchronized use of a broad spectrum of instruments that are well-designed to stay below the thresholds of detection, attribution and retaliation. Combining these (relatively cheap) threats with conventional military hard power confronts the liberal democracies with a difficult choice in terms of defence budget allocation. Whereas arms race stability in the conventional and nuclear domain leads to a peaceful stalemate, this article demonstrates that adding hybrid threats to the spectrum of state power projection leads to a gradual shift of the power balance. While hybrid threats have been extensively studied within the international relations literature, we are (to the best of our knowledge) the first to study these changing security paradigms from a defence economic point of view. Moreover, this article is the first to represent this increasingly complicated state power competition in a game theoretic framework.